EFFECT OF MOMORDICA CHARANTIA FRUIT ETHANOLIC EXTRACT ON MALONDIALDEHYDE (MDA) LEVEL IN BLOOD OF SPRAGUE-DAWLEY RATS INDUCED BY 7,12-DIMETHYLBENZ[A]ANTHRACENE - Ongky Surya Wijaya Hendro; Eka Yudhanto; Ari Budi Himawan; Dea Amarilisa Adespin (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2022)
Background: Cancer is a type of disease with a high rate of diagnostic cases. The real cause of cancer remains unknown. Free radicals can cause cancer by DNA’s gen mutation. 7, 12- Dimethylbenz[a]anthracene (DMBA) is often used for researching carcinogenesis. Many types of research have used natural substances as supportive cancer therapies including Momordica charantia (bitter melon). Malondialdehyde (MDA) is one of the oxidative damage biomarkers which can significantly increase, especially on breast cancer patients. The success of therapy on a breast cancer patient is shown by decreasing MDA levels in the blood. Aim: To investigate the effect of Momordica charantia fruit ethanolic extract on malondialdehyde levels in the blood of Sprague Dawley rats induced by 7,12- Dimethylbenz [a] anthracene. Methods: This study was a true experimental randomized post-test only with control group design on rats that divided into two groups: X1 given DMBA induction only and X2 given DMBA induction with Momordica charantia fruit ethanolic extract by feeding tube with 200mg/kgbw/day for 14 days. Results: The mean of MDA level in group X1 = 0,83±0,32 and in group X2 = 0,30±0,19. The result of the normality test of data using the Shapiro-Wilk test obtained abnormal distribution data for one of the groups. The result of independent-samples T-Test showed a significant difference with P = 0,001. Conclusion: There was an effect of Momordica charantia fruit ethanolic extract on MDA level in the blood of Sprague-Dawley induced by 7,12- Dimethylbenz[a]anthracene.